Application of hypnosis, yoga and relaxation techniques in the treatment of Post-traumatic Stress Disorder – literature review - Rybak, Julia; Pawłowski, Piotr; Sadłowski, Bartosz; Bieganek, Paula; Łukaszewicz, Stanisław; Kordialik, Jakub; Koćwin, Julia; Sarnacka, Sandra; Tokarski, Michał; Tokarska, Angelika (Quality in Sport, 2024)
Introduction and Purpose:Post-traumatic stress disorder (PTSD) presents a complex clinical picture, making treatment challenging. Current pharmacological approaches predominantly target the serotonin system, yet treatment efficacy remains variable. Growing interest in non-pharmacological approaches arises from challenges in identifying effective drug treatments. Dysregulation of the autonomic system and respitarory irregularities highlight the potential of relaxation methods in managing PTSD symptoms. Our study aims to assess the efficacy of unconventional methods such as hypnosis and relaxation techniques as complementary or alternative treatments for PTSD. The State of Knowledge:Numerous studies demonstrate significant reductions in negative PTSD symptoms, particularly re-experiencing, avoidance, and excessive anxiety, through relaxation techniques, meditation, and mindfulness interventions. Promising results are seen in both adult and pediatric populations affected by trauma.. Hypnosis-assisted therapy shows potential in alleviating anxiety, dissociation, and sleep disturbances. Breathing yoga and mindfulness-based therapy also show promise in reducing PTSD symptoms, although further research is needed. Conclusion:Our review underscores the potential of non-pharmacological interventions, like hypnosis, yoga, mindfulness, and relaxation techniques, in alleviating PTSD symptoms. Despite study limitations, these approaches offer valuable adjunctive therapies. Future research should focus on validating their efficacy through well-designed trials. Integrating these techniques into treatment plans could enhance overall well-being for individuals with PTSD, bearing in mind the importance of individualized care.